Critical theory according to the anthropological perspective - Khalaf, Nour; Al-Hasani, Ahmed (Al-Adab Journal, 2025)
Our Arab society and our Iraqi society in particular need debate (critical theory) and this type of thinking, and this is what Marcuse emphasizes in his book (Reason and Revolution) He does not aim to revive Hegel as much as he revives a mental property that he fears is in danger of being lost, which is the ability to think negatively, as we do not have the ability to (think negatively) about many of the negative Western issues and phenomena that are foreign to Iraqi society, especially after 2003, but rather there was an idea of ​​admiration and fascination with the degrading Western content and submission, and the word (negativity or negative view) in our society has become synonymous with humiliation, submission, satisfaction and surrender, and it is devoid of all positivity, effectiveness and will, and the negative view does not mean harsh criticism, voluntary intervention and positive effectiveness, not only for the sake of denying a subject, but perhaps also killing it from its roots, and we notice the negative view of the Arab countries towards (the issue of Gaza and its extermination), as the countries were subjugated and surrendered to the colonial West for its interests. It is necessary to revive the kingdom of negation (criticism) that we have completely lost, as all our lives are positive and accepting. We know nothing about negation at all, as negation is evidence of the individual’s independence, his entity and his progress. That is why critical (dialectical) thought is the thought that agrees with democracy in political life. It is necessary to get rid of the stagnation and lethargy of the mind that indicates the stinginess of the educated person who has become a slave to Western culture and civilization or the previous culture. Either because of intellectual sterility or thinking about personal interest, it is necessary to resort to the dialectical mind, and we live in a modern society because it helps us to build all knowledge, because there is a lot of knowledge and information that is not a subject of question and ultimately turns into an epistemological obstacle that hinders the progress of knowledge.